BAHASA MOTIVASI GURU BAHASA INDONESIA DALAM PROSES PEMBELAJARAN DI KELAS X SMA TRI BHAKTI PEKANBARU - Meri Gusti Rahayu; Dudung Burhanuddin; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research titled language of Indonesian motivation of the teacher in the learning process in class X SMA Tri Bhakti Pekanbaru. The aim of this study is to describe how the motivation used by Indonesian teachers in the learning process in classroom X SMA Tri Bhakti Pekanbaru. This type of research is a qualitative data. The source of is this study the language of the motivation told bye the data. The source of in this study is the language of motivation told by the teacher to the students learning process in class.X. based on the researct found 62 motivational data in the form of rivalry, ego-involvement, praise, punishment, and the desire learn. (1) give skor 0 data, (2) reward 0 data, (3) rival/competition 18 data, (4) ego-involvement 19 data, (5) give repcation 0 data, (6) know that result 0 data, (7) praise 9 data, (8) punishment 9 data, (9) desire to learn 9 data, (10) interest 0 data, (11) purpose recogrized 0 data. The result of the study in the form of motivation data contained in the learning process in class X SMA Tri Bhakti Pekanbaru.Keywords: motivation, Indonesian language teacher, grade X, SMA Tri Bhakti Pekanbaru